2016
DOI: 10.1177/0004563216653762
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin is a potential prognostic marker for polycystic ovary syndrome

Abstract: Background Calprotectin is an antimicrobial, calcium and zinc-binding heterocomplex protein and has been proposed as a marker to rule out inflammatory conditions. The aim of this study was to evaluate the role of calprotectin in the diagnosis of polycystic ovary syndrome and to investigate the association between calprotectin and insulin resistance. Methods A total of 41 females with polycystic ovary syndrome and 54 age-matched without polycystic ovary syndrome were eligible for the study. Serum concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(38 reference statements)
2
4
0
Order By: Relevance
“…There are 2 studies in the current literature on the relationship between PCOS and calprotectin levels. In the first study, Chen et al [ 16 ] found that serum calprotectin levels were significantly increased in PCOS patients and positively correlated with the HOMA-IR index, similar to our study. However, its relationship with hyperandrogenism was not indicated in this study, unlike that in our study.…”
Section: Discussionsupporting
confidence: 91%
“…There are 2 studies in the current literature on the relationship between PCOS and calprotectin levels. In the first study, Chen et al [ 16 ] found that serum calprotectin levels were significantly increased in PCOS patients and positively correlated with the HOMA-IR index, similar to our study. However, its relationship with hyperandrogenism was not indicated in this study, unlike that in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, circulatory lipopolysaccharides increase in blood, triggering the immune system, ultimately resulting in insulin resistance [ 26 ]. Calprotectin binds calcium and zinc and exhibits antimicrobial properties [ 49 ]. Fecal calprotectin, therefore, can be used to gauge inflammation and permeability in the gut [ 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fecal calprotectin, therefore, can be used to gauge inflammation and permeability in the gut [ 48 , 50 ]. In one study, it was observed that serum calprotectin was significantly elevated in patients with PCOS relative to controls, and calprotectin levels were correlated with insulin resistance [ 49 ]. We observed that the TRF diet reduced fecal calprotectin levels.…”
Section: Discussionmentioning
confidence: 99%
“…33 Calprotectin is positively associated with insulin resistance, while androgens (dehydroepiandrosterone sulfate and testosterone) and calprotectin together are elevated in inflammatory disease. 34 Neutrophils can held microbial infection control by phagocytosis and release of anti-inflammatory molecules, 35 whereas about 50% of the cytoplasmic protein content of neutrophils is comprised of calprotectin. 24,36,37 Thus, the calprotectin upregulation in AV may be resulted from the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%